Enhancing vegetable yield and quality with biochar: prospects and challenges - Xu, Xiaoli; Wang, Haiyan; Egun, Ishioma Laurene; Gan, Tao; Huang, Zefeng; Liu, Hui; Gustave, Williamson; Zhang, Xiaokai (Frontiers in Sustainable Food Systems, 2025)
In the context of global climate change, biochar has been recognized as a multifunctional soil amendment that supports sustainable agricultural development and increases vegetable yields. However, there is a lack of comprehensive review of how biochar affects vegetable yields and the potential risks associated with its application. Thus, in this paper, we systematically review the physical, chemical, and biological properties of biochar, as well as its effects on vegetable growth, by optimizing soil structure, enhancing nutrient adsorption, regulating microbial communities, and improving vegetable stress tolerance (e.g., drought and salt resistance). The properties and performance of biochar are dependent on the type of raw material feedstock, pyrolysis temperature, and soil environmental conditions. Although studies have shown that biochar can significantly increase vegetable yield and improve vegetable quality, the high nitrogen content in environments or over-application may cause adverse effects, including the potential release of pollutants, posing environmental risks, and requiring strict quality control during application. Thus, future research is necessary to thoroughly explore the synergistic mode of biochar and organic fertilizer, the development of modified composite materials, and precise application technology to balance the ecological and economic benefits. This review provides the theoretical basis and technical reference for the scientific application of biochar in vegetable production, which is of great significance in achieving sustainable agricultural development.